An Indonesian Experience, Consumers’ Demand For Cng Compression Facilities Performance - Yusep K Caryana (Scientific Contributions Oil and Gas, 1998)
Compressed Natural Gas (CNG) has been used to fuel vehicles in many countrie, including in Indonesia. However, there are many difficulties to overcome in CNG public acceptance. In Indonesia, one of these may be CNG consumer’s preference for certain CNG refuelling stations over others. Finding causes of this may help increase acceptance of CNG by Indonesian motorists and enable CNG to make a better contribution to achievingthe country’s energy diversification policy. It is hypothesized that the variation in intake pressures at CNG station to be a cause for preference by CNG consumers. This hypothesis is based on the variation in total energy of CNG delivered at the point of sale as a result of CNG compressor capacity. It is found that, when the gas system pressure was less than CNG station intel design pressure, the CNG produced in the fuel tank would not reach its design pressure. Consequently, its total energy per fuel tank and payback period of compression facilities investment was affected.The analysis of CNG acceptance and a correlation with CNG station intel design pressure and gas composition from the consumers’ point of view will examine the following factors:The effect of various intel pressure at CNG stations on the performance of existing CNG compressors and after-cooler.The effect of CNG compressor discharge conditions and after-cooler performance on the total energy of CNG delivered to the fuel tank which in turn affects the heating value of the fuel to the vehicle engines.Evaluation of CNG compressor discharge conditions effecting the payback period of CNG station investment and determination of potential significance to compression facilities acceptance.